SIMPLIFIED MATHEMATICAL MODEL OF THERMAL RESPONSE IN ABDOMEN AFTER ABDOMINOPLASTY - Balmant, W.; Carraro, E. (Revista de Engenharia Térmica, 2024)
The search for beauty and perfection brings with it an increase in the number of plastic surgeries. Thus, there is a need for effective postoperative approaches and immediate observation of possible complications, which can lead to more efficient procedures. Among the plastic surgeries, the aforementioned study selected the abdominoplasty surgery as a reference and a certain area 12 x 12 cm, assuming a size in the infra umbilical region, which will supposedly be in the process of tissue repair and with possible temperature changes on the skin surface. The creation of a simplified 2D mathematical modeling to predict the thermal response of the abdomen is presented here. The model considers the local metabolic activities of a healthy skin before the surgical intervention and after it, considering an obstruction of blood flow at a certain point. The model considers such changes by applying mass and energy conservation equations where the amount of O2 supplied regulates the local temperature. Therefore, the reduction of oxygen supplied to the tissues causes a drop in the local temperature representing poor circulation. Decreased local temperature can cause tissue death. Determining the period of low metabolism can be crucial for choosing a treatment and avoiding complications, financial expenses and suffering.